Preparation and Absorption Carbon Monoxide Properties of a Novel Flame Retardants Based Fire-Fighting Foam - Li, Xiujuan; Guo, Ruisong; Qian, Xiaodong (Frontiers in Materials, 2021)
The toxicity of CO threatens the life of people in the fire site. In this study, flame retardants of nano magnesium hydroxide particles and water-soluble flame retardant 8124 are used to be mixed into the aqueous film forming fire extinguishing agent (AFFF). Smoke-suppressed fire extinguishing agent was prepared in Waring-Blender mixing cup and then stirred at 3,000 r/min for 5 min. The new extinguishing agent shows a good performance of absorption of CO and reducing the flue gas temperature. The concentration of CO was decreased below 131 ppm and flue gas temperature was basically kept below 40°C, which was 367 ppm and 83.1°C less than that in free-fire. Using new extinguishing agent can effectively reduce the harm to the trapped personnel and firemen in the fire site. It was of great significance. The harm of CO concentration below 131 ppm and flue gas temperature below 40°C was low. The time to reach the maximum CO concentration and the maximum flue gas temperature was delayed, which ensures that people have more time to escape. Even if there was not enough time to escape, people will not be seriously threatened.